Coordination of Lower Limb During Gait in Individuals With Unilateral Transfemoral Amputation - Mingyu Hu; Yufan He; Genki Hisano; Hiroaki Hobara; Toshiki Kobayashi (IEEE, 2023)
Understanding the lower-limb coordination of individuals with unilateral transfemoral amputation (uTFA) while walking is essential to understand their gait mechanisms. Continuous relative phase (CRP) analysis provides insights into gait coordination patterns of the neuromusculoskeletal system based on movement kinematics. Fourteen individuals with uTFA and their age-matched non-disabled individuals participated in this study. Kinematic data of the lower limbs of the participants were collected during walking. The joint angles, segment angles, and CRP values of the thigh-shank and shank-foot couplings were investigated. The curves among the lower limbs of the participants were compared using a statistical parametric mapping test. Compensatory strategies were found in the lower limbs from coordination patterns. In thigh-shank coupling, although distinct coordination traits in stance and swing phases among the lower limbs were found, the lower limbs in both groups were discovered to remain in a similar coordination pattern during gait. For individuals with uTFA, in shank-foot coupling, intact limbs demonstrated a short period of foot-leading pattern which was significantly different from that of the other limbs during mid-stance to compensate for the weaker force generation by prosthetic limbs. The findings offer normative coordination patterns on the walking of individuals with uTFA, which could benefit prosthetic gait rehabilitation and development.